Peranan Akun Twitter @Txtdaripemerintah Sebagai Ruang Publik Bagi Masyarakat Dalam Perspektif Komunikasi Di Media Sosial - Shinta Hartini Putri; Leoni Oktavia Maharani (Universitas Informatika dan Bisnis Indonesia, 2021)
New media, especially social media, are often used by various levels of society, because social media is not only a channel of information or a means of entertainment, but more than that social media is a public space that allows people to know, give opinions, correct and criticize all forms of information development or issues that occurred. One of the social media that has become a public space is Twitter, in this study, in particular, the Twitter account @txtaripemerintah. The account is a base that accommodates and uploads all forms of information in the form of news and statements from the government from online news portals. The @txtdaripemerintah account carries out its function as a public space so that the public can find out, correct and express their opinions regarding current issues. This study uses descriptive qualitative research methods, with primary data collection techniques through observation through the twitter account @txt from the government, while secondary data uses library research, journals, and internet sources. The output of this research will be published in the Artcomm Online Journal, Faculty of Communication and Design, UNIBI. The target of research results is expected to be the completeness and analysis of data in the research environment.